Rapid magnetic separation: An immunoassay platform for the SERS-based detection of subarachnoid hemorrhage biomarkers - Wang, Ying; Sun, Jingyi; Zhao, Peng; Yi, Hui; Yuan, Hui; Yang, Mingfeng; Sun, Baoliang; Che, Fengyuan (Frontiers in Chemistry, 2022)
Blood-brain barrier (BBB) is of vital importance to the progression and prognosis of subarachnoid hemorrhage (SAH). The construction of a simple, sensitive, and accurate detection assay for measuring the biomarkers associated with BBB injury is still an urgent need owing to the complex pathogenesis of SAH and low expression levels of pathological molecules. Herein, we introduced surface-enhanced Raman scattering (SERS) labels embedded Fe3O4@Au core-shell nanoparticles as ideal SERS sensors for quantitative double detection of MMP-9 and occludin in SAH patients. Meanwhile, utilizing the SERS signals to dynamic estimate MMP-9 and occludin concentration in rat SAH model, is the first application in exploring the relationship of pathological MMP-9 and occludin molecular levels with neurobehavioral score. This method warrants reliable detection toward MMP-9 and occludin with a wide recognition range and a low detection limit in blood samples. Furthermore, the results monitored by SERS assay were exactly matching with those obtained through traditional enzyme-linked immunosorbent assay (ELISA). The above results demonstrated this novel biosensor strategy has extensive application prospects in quantitative measurement of multiple types of biomolecules in body fluids samples.